Interfacial Bond Behavior of Clay Brick Masonry Strengthened with CFRP - Zhen Lei; Hui Ma; Yumin Luo; Enmao Wang; Haiyan Huang; Li Zhang (Buildings)
This study investigates the interfacial bond behavior of clay brick masonry strengthened with carbon fiber-reinforced polymer (CFRP) through single-side shear tests. Two specimen types (single bricks and masonry prisms) were tested under varying parameters, including bond length, bond width, mortar joints, and end anchorage. Experimental results revealed cohesive failure within the masonry substrate as the dominant failure mode. Mortar joints reduced bond strength by 12.1–24.6% and disrupted stress distribution, leading to discontinuous load–displacement curves and multiple strain peaks in CFRP sheets. Increasing bond width enhanced bond capacity by 16.3–75.4%, with greater improvements observed in single bricks compared with prisms. Bond capacity initially increased with bond length but plateaued (≤10% increase) beyond the effective bond length threshold. End anchorage provided limited enhancement (<14%). A semi-theoretical model incorporating a brick–mortar area proportion coefficient (χ) and energy release rate was proposed, demonstrating close alignment with experimental results. The findings highlight the critical influence of mortar joints and provide a refined framework for predicting interfacial bond strength in CFRP-reinforced masonry systems.